Beyond motivation: Job and work design for development, health, ambidexterity, and more - Parker, Sharon (2014)
Much research shows it is possible to design motivating work, which has positive consequences for individuals and their organizations. This article reviews research that adopts this motivational perspective on work design, and it emphasizes that it is important to continue to refine motivational theories. In light of continued large numbers of poor-quality jobs, attention must also be given to influencing practice and policy to promote the effective implementation of enriched work designs. Nevertheless, current and future work-based challenges mean that designing work for motivation is necessary but insufficient. This review argues that work design can be a powerful vehicle for learning and development, for maintaining and enhancing employees' physical and mental health, and for achieving control and flexibility simultaneously (for example, in the form of ambidexterity); all these outcomes are important given the challenges in today's workplaces. The review concludes by suggesting methodological directions.